Evolution of the mechanical properties of a tropical soil stabilized with lime and ash of rice rind - De Morais Alcantara, Marco Antônio [UNESP]; Dos Santos, Lucas Pereira; De Lima, Dario Cardoso (My University, 2010)
The ash of rice rind is a pozzolanic material that reacts with the calcium hydroxide (Ca (OH)2) forming bonding composites, when finely worn out and in water presence. Considering this behavior, the objective of the present work was to evaluate the potential use of this residue in the enrichment of the content of pozzolanic materials of a tropical soil stabilized with a commercial hydrated lime. The laboratory testing program incorporated unconfined compression strength tests performed on the soil and on its mixtures with contents of 8% of lime enriched with 5 and 10% of ash of rice rind in relation to the soil dry mass. The results of the testing program supported that the use of the residue was effective in increasing the degree of reactivity of the soil that was also directly related with the increase in the ash content and the period of cure of the mixtures.
Keywords: Enrichment of pozzolanic activity; Mixture unconfined compressive strength; Soil improvement; Soil-lime-ash of rice rind mixture; Ash contents; Calcium hydroxides; Laboratory testing; Pozzolanic activity; Pozzolanic materials; Testing programs; Tropical soils; Unconfined compression strength; Calcium; Cements; Compressive strength; Hydrated lime; Hydrates; Lime; Mechanical properties; Mixtures; Soils; Testing; Soil testing